Vándorévek külföldön – A Budapesti Műszaki Egyetem hallgatóinak és tanárainak tanulmányútjai 1899 és 1914 között - Tar, Attila (Gerundium, 2017)
The study-tours of students and teachers from the Technical University of Budapest 1899–1914. The Technical University of Budapest was a young institution by the end of the 19th century. It was officially founded in 1871, even though it had appeared in some forms from the 1840s. The Hungarian technical schools looked to copy the German model. To accomplish this they needed information about this type of higher education. Through studying the historical records it is possible to detect several forms of informationcollection, which can be seen as forms of communication. The Technical University of Budapest used to ask the German Technical Colleges and Universities about different matters in letter-form. Another form of this communication was the arranging of excursions to the partner-universities. Next, we can mention the doctor „honoris causa” awards, and furthermore the membership of Hungarian professors in German scientific academies or societies. And lastly are the study tours of students and teachers to mention. The visits by Hungarian students and professors from the Technical University of Budapest to European destinations were analysed, the purpose of which was to gather experience. It was a good period for such visits: the Hungarian government supported the studies, the part-time studies and the study-tours of Hungarian students and professors abroad. These studies usually involved the visit of factories, public institutions and scientific institutes. The students of the Technical University showed active participation in these projects. The main destination of these tours was Germany, sometimes as part of a complex Central-European journey. The participants applied for a scholarship, granted usually by the Ministry for Education and Religion. It is worth seeing the method of applying for scholarships, the rules for the finances and the final reports on record. In the study these parts of the procedure are shown and the aim of these efforts is also highlighted: to benefit the Hungarian industry and transportation.